An Active Control with a Magnetorheological Damper for Ambient Vibration - Laixi Zhang; Chenming Zhao; Feng Qian; Jaspreet Singh Dhupia; Mingliang Wu (Machines, 2022)
The ambient vibration in manufacturing and assembly plants caused by nearby large equipment or heavy vehicles can produce dynamic machining error and even generate chatter in machining systems such as robotic drilling systems. In this paper, we present an active control method with a magnetorheological damper (MRD) for reducing ambient vibration in a robotic machining system, with the advantages of wider frequency bandwidth and robustness. A sliding mode control (SMC) algorithm is proposed as well. The control performance of the SMC under different excitations is simulated by Simulink and compared with that of the PID control algorithm; the result shows that the SMC is superior to the PID control and passive vibration control. An MRD is designed based on the control force of the active vibration control in the time domain in order to provide the required damping force. The results of co-simulation using ADAMS and Simulink verify that the ability of the SMC to control vibration performance is significantly improved compared with that of the passive vibration control.